2019
DOI: 10.30983/educative.v4i1.1333
|View full text |Cite
|
Sign up to set email alerts
|

Reading Interest and Reading Comprehension : A Correlational Study

Abstract: <p class="abstrak"><em>The objective of this research was to find out the correlation between students’ reading interest and reading comprehension. The method used in this study was quantitative and the technique used was a correlational study. The population of the research was taken from students of the eighth grade of SMP Ahmad Dahlan Kota Jambi. The numbers of the population were 47 students. The Total sampling </em><em>which used all the population </em><em>was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
2
8
0
3
Order By: Relevance
“…The results of the current investigation reveal a similar perspective in previous studies regarding the relationship between students' reading interest and reading comprehension (Rumaniah, 2018;Despita, 2020;Fitria, 2019). Therefore, in this study the author only focuses on elaborating the relationship between reading interest and reading comprehension for undergraduate students.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of the current investigation reveal a similar perspective in previous studies regarding the relationship between students' reading interest and reading comprehension (Rumaniah, 2018;Despita, 2020;Fitria, 2019). Therefore, in this study the author only focuses on elaborating the relationship between reading interest and reading comprehension for undergraduate students.…”
Section: Discussionsupporting
confidence: 85%
“…After the researcher conducted an analysis using the SPSS 25.0 version program to calculate the correlation, it was found that there was a significant positive relationship between students' reading interest and reading comprehension. In addition, it was found in the results of Pearson Product Moment that the relationship between reading interest and reading comprehension was categorized in a weak relationship Considering the finding of the correlation analysis, the current study has the same significance as the results of research conducted by Fitria (2019) and Despita (2020). Their study mentioned that it has a significant correlation between students' reading interest and reading comprehension.…”
Section: Discussionsupporting
confidence: 64%
“…Previous researchers have conducted a research and it showed the same result with this current research. Fitria (2019) found a significant correlation between students' reading interest and reading comprehension in SMP Ahmad Dahlan. The coefficient correlation of reading interest and reading comprehension was 0.983.…”
Section: Pair-wise Correlations Of Reading Interest Reading Self-effmentioning
confidence: 76%
“…They reported that reading cognition could improve the students' sense of a text, motivating, and word stock (Farha & Rohani, 2019). If the students understand the vocabulary, they can easily comprehend the text and build their reading interest (Fitria, 2019). Targets several things, including motivation and repetition, help students understand their reading comprehension (Rumainah, 2018).…”
Section: The Relationship Between Reading Interest and Vocabularyacquisitionmentioning
confidence: 99%
“…Reading also makes a person more innovative and more creative. A study conducted by Fitria (2019) stated that when students comprehend what they are reading, the more they read, the better they understand each word meaning in English (Fitria, 2019).…”
Section: Introductionmentioning
confidence: 99%